Principles of Justice and Legal Certainty by election organizers Regarding Conditions for Nominating Regional Heads - DJulham Djaguna; Sultan Alwan; Irham Rosyidi (Journal Equity of Law and Governance, 2024)
This study aimed to understand the considerations of the judges of the Honorary Council for Election Organizers (DKPP) in handling cases of violations of law and ethics by regional head election organizers, as reflected in the 161-PKE-DKPP/XI/2020 decision. This study adopted a normative or doctrinal legal research method, utilizing primary, secondary, and tertiary legal materials. Analysis was conducted through a theoretical descriptive approach to the problem faced. The results showed that the DKPP judges criticized the South Halmahera KPU for its lack of professionalism in examining the nomination requirements, stating that the KPU should not only understand the nomination PKPU and Juknis textually, but also substantively. The DKPP judge's decision showed high professionalism, prudence, and wisdom, with deep consideration based on existing norms. However, in terms of rejecting the fulfillment of the nomination requirements, the South Halmahera KPU also had applied the principle of legal certainty which is considered the appropriate legal norm in the context of the South Halmahera district head election.